Porencephalic cyst: a rare cause of new-onset seizure in an adult - Anam Qureshi; Asad Jehangir; Eugene P. York (Greater Baltimore Medical Center, 2018)
We present a case of a 56-year-old male with a history of perinatal intracerebral hemorrhage who presented to the emergency department after a witnessed new-onset generalized tonic-clonic seizure. Computerized tomography and magnetic resonance imaging of the head revealed a large frontal lobe porencephalic cyst, with encephalomalacia in the right parietal lobe and temporal lobe (the patient did not have any prior cranial imaging). The patient has subsequently remained seizure-free on levetiracetam. Porencephalic cyst is a rare condition of cerebrospinal fluid accumulation in the brain parenchyma that is usually related to perinatal vascular events. These cysts can have a wide array of clinical presentations. This can include partial or generalized seizures, which are usually managed by antiepileptics.